THE CONCEPTS OF «VOCATIONAL EDUCATION AND TRAINING» IN THE NATIONAL RESEARCH AREA - Hryshchuk, Yuliya V. (Educological discourse, 2014)
In the article described the features of professional education and training in Ukraine. The experience of Ukraine’s international cooperation in the field of professional education and training as part of a pilot project of the European Training Foundation «Turin process – regional level». The researcher analyzed activity agencies of the European Union in the field of education and professional development.